STRATEGY ANALYSIS FOR IMPROVING SERVICE QUALITY IN THE PHARMACY DEPARTMENT AT HOSPITAL - Naniek Widyaningrum; Sampurno Sampurno; Djoko Wahyono (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The Hospital of Army Semarang is a hospital with a strategic location and its Pharmacy Department Swadana has competitive pharmaceutical prices. But, patients from the surrounding communities visiting for treatment in the hospital is less than those in its competitor. The aims of this research were to analyze internal and external conditions and also to evaluate the quality of service delivery in self financing Pharmacy Departement. This research was non experimental research, used quantitative and qualitative methods. Quantitative research measured patient’s satisfaction measured using SERVQUAL questionnaire. Dispensing time was calculated from duration of receipt service, and compare to standard procedures. Qualitative research analyzed internal and external conditions. Result of the research was formulated in a SWOT matrix used as input for the self financing strategic planning of improving the quality of service delivery in the Pharmacy Department in the Hospital of Army. Results of the research indicated that based on all the three indicators, there were unsatisfaction among outpatients, and medical and paramedical staffs in the Hospital of Army, which could be seen from negative gap in all the dimensions of questionnaires. The duration of receipt service was in accordance with public service standards, and the Pharmacy Department did not have a written service standard procedures. From the SWOT analysis, it can be known that the hospital has strenghts, namely, a strategic location and competitive prices, and weaknesses such as the lack of quality and quantity of human resources, opportunity for government to provide public service, and threats such as an increasingly tight business competition and progression of science and technology. It is recommended that the Pharmacy Department of the hospital should increase the coverage and scope of service delivery through promotion and counseling, improve the quality of service delivery, equip the department with adequate physical infrastructures and improve the quality of human resources through education and training.Keywords: SWOT, SERVQUAL, Pharmacy Department